2004
DOI: 10.1080/00140130412331290862
|View full text |Cite
|
Sign up to set email alerts
|

The ergonomics of different tyres and tyre pressure during wheelchair propulsion

Abstract: It is believed that the newer solid tyres on wheelchairs perform as well as pneumatic tyres along with less cost and time for maintenance. The questions are: (1) do solid tyres perform as well as pneumatic tyres and (2) what is the critical level of pneumatic tyre pressure before wheeling efficiency decreases? Part one measured the rolling resistance differences of five commonly used wheelchair tyres (three pneumatic and two solid) under four different tyre pressures (100, 75, 50 and 25 of inflation). Part two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 5 publications
7
47
0
1
Order By: Relevance
“…Moreover, pneumatic tires with different inflation levels have been shown to have different rolling resistances [3]. By using the same type of pneumatic tires, Sawatzky et al found that a tire inflated to 100 percent had significantly less rolling resistance than tires inflated to 50 percent, but did not find a difference comparing tires inflated to 100 and 75 percent [3]. Our results both corroborate and extend these results to add to the knowledge about tire inflation.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Moreover, pneumatic tires with different inflation levels have been shown to have different rolling resistances [3]. By using the same type of pneumatic tires, Sawatzky et al found that a tire inflated to 100 percent had significantly less rolling resistance than tires inflated to 50 percent, but did not find a difference comparing tires inflated to 100 and 75 percent [3]. Our results both corroborate and extend these results to add to the knowledge about tire inflation.…”
Section: Discussionsupporting
confidence: 86%
“…Prior studies have reported that tire type and pressure influence rolling resistance and thus can change propulsion effort [3,10,13]. Pneumatic tires have been shown to have lower rolling resistance than solid tires [10,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the solid tires exhibited significantly higher RP values than the pneumatics. Considering that the solid and pneumatic rear wheels had similar radii, the fact that the former exhibited a higher RF than the latter is consistent with the previous results [5][6]27]. Thus, even if solid tires do not need to be maintained, improvements in their materials are required to reach the rolling properties of pneumatic tires.…”
Section: Modeling the Mwc Rolling Resistance (Equation 4)supporting
confidence: 80%